Investigating the Factors Affecting Women's Political Participation in Nepal: A Qualitative Study - Bajimaya, Prabhat (Journal of Public Representative and Society Provision, 2022)
This research aims to examine the factors that have influenced women political participation in Nepal using qualitative approach by conducting case study interviews with Females that have served in political leadership capacity. The study shows that legal reforms in particular the ones in the region are still are limited in addressing gender equity, as deeply rooted cultural practices as well as perceived economic realities still confine women to the lower tiers of political activity. The work specifies such obstacles as the obvious ones, such as gender prejudices, lack of funds, and violence, and others, including support from a mentor and relatives, financial and institutional support. These work somewhat shifts the dominant notions of political participation showing that an intersectional approach should encompass all the identities and statuses connected to gender. The study also points out the inadequacy of the quotas in stating that though they enhance tokenism, they require other structural and cultural changes for genuine Girl Empowerment. Overall, this research informs theoretical debates of women and politics and provides policy prescriptions on how a better future can be created for women’s political involvement in Nepal. The findings therefore have potential lessons for policy makers, advocates and scholars involved in feminists struggles for women representation in politics internationally.